How Psychological Well-Being Links to Organizational Commitment: Insights from Educational Personnel at Jambi University - Beny Rahim; Fadzlul; Rion Nofrianda; Jelpa Periantalo; Verdiantika Annisa (Side: Scientific Development Journal, 2025)
Mental health is a concern nowaday in workplace. For instance, psychological well-being owned by educational Personnel at Universitas Jambi. Psychological well-being is the ability to understand and accept one's qualities, have positive relationships with others, be able to live independently, be able to set goals in life and be able to adjust to the surrounding environment.  Support from the institution is needed so that employees can continue to be productive so that they still want to continue to be part of the organization or often referred to as organizational commitment. Therefore, this study aims to see the relationship between psychological well-being and the commitment of educational staff organizations within the University of Jambi. The subject of this study is all of education staffs at the University of Jambi with at least 1 year of teaching experience. Using the techiniques by Ryff in 1989, non-probability sampling techniques with purposive sampling techniques. Psychological well-being was measured by the psychological well-being scale (reliability 0.943) and organizational commitment was measured using the organizational commitment scale (reliability 0.813). The results of data analysis using Pearson Product Moment showed  a significant positive relationship (0.001 < 0.05) with a Pearson correlation value  of 0.429. This shows that when education staffs have increased psychological well-being, it will make their commitment to stay in the organization even stronger.